Relationship between immune nutrition index and all-cause and cause-specific mortality in U.S. adults with chronic kidney disease - Zhang, Junlin; Xiao, Xiang; Han, Tianzhao; Liu, Yuping; Shuai, Ping (Frontiers in Nutrition, 2023)
1. This is the first study to investigate the associations of several immunonutrition indices including PNI, SIS, CONUT and NPS, with mortality in U.S. adults with chronic kidney disease; 2. The PNI was the best indicator for predicting the mortality in CKD and the cutoff value was 51; 3. PNI was positively associated with eGFR and lymphocyte to monocyte ratio (LMR), and negatively correlated with UACR and neutrophil lymphocyte ratio (NLR) in CKD; 4. PNI was an independent predictor for all-cause and CVD mortality in CKD individuals.